Design of New Student Registration Information System at SMPN 3 Kecamatan Payakumbuh - Fitri Rahmadani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
In this research, the author encountered some problems with PPDB (admission of new students) in SMP N 3 Kecamatan Payakumbuh, as there was no website for new student registration. As a result, the announcement about the PPDB was announced through brochures. Sometimes, this makes a problem, such as a brochure was lost or torn. Therefore, there were obstacles to administration and information about the PPDB, it made inefficient. Another problem was that there was no data stored in the database, which made data vulnerable to lose and easily burned. Research and Development (R&D) with the system development model used is SDLC (System Development Life Cycle), which consists of 5 stages, namely Communication, Planning, Modeling, Construction dan Deployment. When planning‎[1], the ACON student information system was built using PHP/MySql. The research was tested using a validity test with three validators, and the system was declared valid with an average of 0.78. Furthermore, the system was declared very practical with an average of 0.97 after being tested on three teachers. At last, the effectiveness test was conducted on 5 students, and the system received a very high effectiveness score of 0.87 on average‎.